A survey of world language cooperating teachers: Implications for teacher development. (6th November 2019) - Moser, Kelly M.; García, Paul A.; Davis‐Wiley, Patricia; Hernández, Todd A.
Abstract: In an era of long‐standing world language teacher shortages, the preservice mentoring process has become even more critical. Using data from a national survey, this study provides a profile of PreK–12 world language cooperating teachers (CTs) and shares their beliefs about and perspectives on the teacher candidates with whom they work, their interactions with postsecondary stakeholders, their reasons for serving as CTs, and the challenges that inhibit the smooth and meaningful induction of new colleagues into the profession. Implications highlight opportunities for reform in world language teacher development. The Challenge: Despite their importance, the role and contributions of cooperating teachers (CTs) in world language teacher development (WLTD) remain underinvestigated. What can the profession learn about who WL CTs are and why they serve in this capacity? How do data from a national survey identify areas for improvement in WLTD?